Proceedings of the 5th International Workshop on Multimedia Assisted Dietary Management 2019
DOI: 10.1145/3347448.3357167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mixed Reality Food Labels on Product Selection

Abstract: The rise in diet-related non-communicable diseases suggests that consumers find it difficult to make healthy food-related purchases. This situation is most pertinent in fast-paced retail environments where customers are confronted with sugar-rich or savory food items. Countermeasures such as front-of-package labelling are not yet mandated in most regions, and barcode scanning mobile applications are impractical when purchasing groceries. We thus applied a mixed reality (MR) wearable headset-mediated interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…MR technology has interesting applications in product selection in retail environments. Fuchs et al (2019) suggested and used the MR headset-mediated food labels (Nutri score) to study the product (beverage and snacks) selection behavior of customers in a vending machine. This kind of approach helped the customers in selecting nutritious products of lesser sugar and energy content.…”
Section: Selection Behavior In Supermarketsmentioning
confidence: 99%
“…MR technology has interesting applications in product selection in retail environments. Fuchs et al (2019) suggested and used the MR headset-mediated food labels (Nutri score) to study the product (beverage and snacks) selection behavior of customers in a vending machine. This kind of approach helped the customers in selecting nutritious products of lesser sugar and energy content.…”
Section: Selection Behavior In Supermarketsmentioning
confidence: 99%